Development and Validation of a Simple RP-HPLC Method for Simultaneous Estimation of Metformin Hydrochloride and Rosiglitazone in Pharmaceutical Dosage Forms - Akteruzzaman, Md; Rahman, Asma; Sultan, Md Zakir; Islam, Farhana; Salam, Md Abdus; Rashid, Mohammad A (Dhaka University Journal of Pharmaceutical Sciences, 2013)
The objective of this study was to develop a simple, efficient, precise and accurate reversed phase HPLC (RP-HPLC) method for simultaneous determination of metformin in combination with rosiglitazone in newly formulated tablets. The combination of these drugs are commonly used and prescribed as anti-diabetic drugs in Bangladesh. The method has been developed by using the mobile phase comprising of sodium dihydrogen phosphate (NaH2PO4) buffer (pH 3.5) and acetonitrile (60:40, v/v) at a flow rate of 0.7 ml/min over C18 bonded silica column (ODS) (250 x 4.6 mm, 5 ?) at ambient temperature. The effluents were monitored at 230 nm and retention times were found to be 3.35 min and 11.95 min for metformin and rosiglitazone, respectively. Calibration curves were determined with a range from 0.03125 to 0.50 ?mole/ml of standards and the regression coefficients (r2) were found as 0.999 for metformin and 1.0 for rosiglitazone. The assay was validated for the accuracy, precision etc. according to ICH, USP and FDA guidelines. The proposed method can be useful in routine analysis for quantitative determination of metformin hydrochloride and rosiglitazone in pharmaceutical dosage forms. DOI: http://dx.doi.org/10.3329/dujps.v11i2.14574 Dhaka Univ. J. Pharm. Sci. 11(2): 157-163, 2012 (December)